2021
DOI: 10.1101/2021.02.23.432450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The proximal proteome of 17 SARS-CoV-2 proteins links to disrupted antiviral signaling and host translation

Abstract: Viral proteins localize within subcellular compartments to subvert host machinery and 25 promote pathogenesis. To study SARS-CoV-2 biology, we generated an atlas of 2422 26 human proteins vicinal to 17 SARS-CoV-2 viral proteins using proximity proteomics. This 27 identified viral proteins at specific intracellular locations, such as association of accessary 28 proteins with intracellular membranes, and projected SARS-CoV-2 impacts on innate 29 immune signaling, ER-Golgi transport, and protein translation. It i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 97 publications
2
9
0
Order By: Relevance
“…Nsp14 may manipulate IMPDH2 to increase the phosphorylation of IKKβ and IκBα to promote nuclear translocation and phosphorylation of p65 (24). In addition, we also noticed that Nsp14 partially localizes in the nuclei of cells (Fig 1C, D), similar to findings from other groups (51,52). Thus, Nsp14 may associate with and modify the host cellular RNAs via its exonuclease and methyltransferase activities.…”
Section: Impdh2 Inhibition Blocks Nsp14-mediated Nf-κb Activation and Il-8 Inductionsupporting
confidence: 84%
“…Nsp14 may manipulate IMPDH2 to increase the phosphorylation of IKKβ and IκBα to promote nuclear translocation and phosphorylation of p65 (24). In addition, we also noticed that Nsp14 partially localizes in the nuclei of cells (Fig 1C, D), similar to findings from other groups (51,52). Thus, Nsp14 may associate with and modify the host cellular RNAs via its exonuclease and methyltransferase activities.…”
Section: Impdh2 Inhibition Blocks Nsp14-mediated Nf-κb Activation and Il-8 Inductionsupporting
confidence: 84%
“…The rs2897075_T allele at 7q22.1, associated with increased IPF and COVID-19 risk, was linked to decreased TRIM4 and ZKSCAN1 expression. TRIM4 is an important regulator of virus-induced interferon induction pathways and a proteomic study identified significant adjacency between SARS-CoV-2 M protein and TRIM4 [13]. Viral infection-induced micro-injury to the alveolar epithelium is thought to be a trigger for development of IPF [14], suggesting the interferon-mediated innate immune response could be central to both risk of chronic lung disease and worse outcomes due to SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…The rs2897075_T allele at 7q22.1, associated with increased IPF and COVID-19 risk, was linked to decreased TRIM4 and ZKSCAN1 expression. TRIM4 is an important regulator of virus-induced interferon induction pathways and a proteomic study identified significant adjacency between SARS-CoV-2 M protein and TRIM4 11 . Viral infection-induced micro-injury to the alveolar epithelium is thought to be a trigger for development of IPF 12 , suggesting the interferon-mediated innate immune response could be central to both risk of chronic lung disease and worse outcomes due to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%